Influência dos herbicidas Sulfentrazone (Boral® 500 SC) e Glifosato (Roundup® Original) na composição bioquímica e nas defesas antioxidantes de Melanophryniscus admirabilis (Anura: Bufonidae) - Silva, Patrícia Rodrigues da (2017)
The increased use of pesticides has caused the degradation of a variety of ecosystems, especially aquatic environments. Despite specific targets, agrochemicals are able to cause metabolic and functional alterations including in non-target organisms. Amphibians constitute the most globally threatened Class of vertebrates, and the population declines observed around the world are due to a synergy of different factors, including habitat degradation and fragmentation, mostly to agricultural purposes, and the exposure to contaminants derived of these activities, among others. Within this context, Melanophryniscus admirabilis is a micro endemic bufonid toad species, with occurrence registered to only one area in Rio Grande do Sul state (Brazil). This species has a critically endangered (CR) status, at regional, national and global levels. The great danger of extinction is due to several factors, including habitat fragmentation (especially for agricultural purposes) and the decreased habitat quality, mainly because of extensive use of agrochemicals in areas near of the natural habitat of this species. In view of the foregoing, the objective of the present study was to analyze possible alterations in metabolic and oxidative parameters in total homogenate of M. admirabilis tadpoles exposed to two different concentrations of commercial formulation containing Sulfentrazone (Boral® 500 SC) and two concentrations containing Glyphosate (Roundup® Original). The total levels of glycogen, proteins and uric acid were analyzed; as well as the possible occurrence of lipid peroxidation (LPO), expressed by TBARS levels; and the enzymatic activity of Superoxide Dismutase (SOD), Catalase (CAT) and Glutathione S-Transferase (GST). The results showed significant alterations in metabolic and oxidative parameters, in groups exposed to Sulfentrazone and Glyphosate herbicides. Analyzing these results, we hypothesize that the associated mobilization of enzymes and metabolic parameters presumably was capable of counter the oxidative lipid damage in these animals. Despite of that, the observed alterations may affect these animals during its life cycle, especially during and after metamorphic period. The apparent enzymatic inhibition observed in groups exposed to the herbicides, in addition to indicate the great susceptibility of tadpoles to these agents, reflects an impairment of the ability of these animals to cope with adverse and synergistic environmental situations, such as habitat fragmentation, UV radiation and exposure to other pollutants. The absence of mortality suggests resistance of M. admirabilis tadpoles to the tested concentrations of herbicides; nevertheless, the comparison of the antioxidant capacity of this species against taxonomically related species would be relevant. Therefore, the present study has demonstrated that the exposure of M. admirabilis tadpoles to sub lethal concentrations of Sulfentrazone and Glyphosate herbicides has affected the homeostasis, thus affecting the survival, of these animals in later life cycle stages. However, further studies would be necessary, including other concentrations and herbicides, as well as the analysis of further metabolites and components of the antioxidant system of this species.